NANOSTRUCTURED COPPER OXIDE THIN FILMS VIA RAPID HYDROTHERMAL ROUTE FOR ELECTROCHEMICAL ENERGY STORAGE (International Journal of Food and Nutritional Sciences, 2022)
This study examines the rapid hydrothermal production of nanostructured copper oxide (CuO) thin films as efficient electrode materials for supercapacitors. Supercapacitors are esteemed for their fast charging and discharging capabilities and elevated power density, making CuO a desirable material owing to its substantial theoretical capacitance, adequate conductivity, and eco-friendliness. Nanostructuring CuO increases surface area and reduces ion diffusion distances, improving electrochemical performance. The synthesis process utilizes a hydrothermal approach that is energy-efficient, cost-effective, and sustainable, using deionized water as a solvent. Critical factors like temperature, pH, and reaction duration are adjusted to produce CuO with nanostructures that enhance electrochemical properties. The synthesized CuO is applied to nickel foam or stainless-steel substrates by dip-coating or electrochemical deposition. Characterization methods include X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM), offering insights into structural and morphological attributes. XRD verifies phase purity, SEM analyzes surface appearance, and TEM elucidates nanostructure dimensions and crystallinity. The electrochemical performance is evaluated by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS). CV investigation reveals pseudo-capacitive behavior, with specific capacitance reaching 60 Fg⁻¹. GCD testing demonstrates efficient charging-discharging characteristics, whilst EIS indicates little internal resistance and advantageous charge transfer. The research finds that hydrothermally produced CuO thin films are advantageous for supercapacitor applications. They offer a sustainable method to create high-capacity, stable, and economical materials for improved energy storage systems.